(untitled) (Research, Society and Development, 2021)
Bisphosphonates (BIS) are indicated for several clinical disorders (e.g., osteoporosis). However, BIS has been associated with osteonecrosis and alterations in osteoclastogenesis and skeletal development. This study aimed to evaluate the effects of BIS (zoledronic acid - ZA and alendronate sodium - AS) on zones of the growth plate of rat femur. Animals (Wistar rats, n = 19) were divided into groups: 1) AS Group: animals received alendronate sodium orally (3 mg/kg per day); 2) ZA Group: ZA was administered intraperitoneally (0.2 mg/kg per week); and 3) Control Group (CG): a vehicle was administered. Animals were euthanized 21 days after the treatment, and femurs were collected for histological analysis. The images of all zones (resting, proliferative, hypertrophic, and calcified) were processed by the Qcapture® software providing a 40 and 400-fold increase. ZA decreased epiphyseal growth plate cell zones (ZA Group vs. CG) in most cases. Likewise, AS diminished the proliferative zone (AS Group vs. CG). Furthermore, ZA increased the calcified zone (ZA Group vs. CG). Previous works demonstrated that BIS decrease the epiphyseal disc. This reduction is probably due to the shortening of the cellular zones that undergoes calcification/ossification. The present results suggest that BIS should be carefully indicated because these drugs might accelerate epiphyseal closure.